CONTENT OF THE CONCEPT OF THREAT AND SOCIETY UNDER THREAT IN THE SYSTEM OF POLITICAL RESEARCH (Scientific journal of the Fergana State University, 2024)
This article talks about socio-economic, political factors and features of the formation of a threat-resistant society. The author analyzes the external and internal forces that threaten the society in the era of globalization, as well as the mechanisms of combating them.